Antifungal compound in lipophilic extractives of Gymnostoma nobile heartwood - Nor Amira, Khurshid Ahmed (Universiti Malaysia Sarawak (UNIMAS), 2014)
Lipophilic wood extractives are chemical compounds that dissolve in fats, oils, lipids and non-polar solvents. Natural dumbility of Gymnostoma nobile heartwood is known to be high. This study examined the antifungal compounds in lipophilic extmctives of Gymnostoma nobile heartwood. The solvents used to extmct lipophilic extractives were hexane and dichloromethane (DCM). The first objective of this study were to determine the amount of hexane and dichloromethane (DCM) extmctives from G. nobile heartwood. Secondly, to evaluate the antifungal properties of lipophilic extmctives obtained from G. nobile and lastly to identify the chemical constituents of hexane and dichloromethane (DCM) extracts from G. nobile heartwood Sequential solvent extraction by using hexane and DCM were carried out. Gas chromatoghraphy-mass spectrometry techniques were used to identify and characterize the chemical constituents and compositions of hexane and DCM crude extmct fractions from G. nobile. The antifungal activities were determined in DCM extracts using agar dilution method. The total hexane extmct of G. nobile was 0.044% while total DCM extmct obtained was 0.365%. For hexane crude extmct, octacosane (54.20%), D-Streptamine (14.23%) and 1,2-Propanediol (13.20%) were the major compounds detected. The major chemical constituents in DCM crude extracts were 9-Borabicyclo [3.3.1] nonane (24.34%), D-Streptamine (19.71%) and 1,2 Propanediol (19.18%). DCM crude extracts from G. nobile were toxic to Trametes versicolor and Gloeophyllum trabeum.